SAT0449 Juvenile onset systemic lupus erythematosus outcome in adulthood: a monocentric retrospective cohort. (12th June 2018) - Pha, M.; Mathian, A.; Haroche, J.; Cohen Aubart, F.; Hié, M.; Huong, D. Lê Thi; Pineton de Chambrun, M.; Kwon, T.; Amoura, Z.
Abstract : Background: Outcome of juvenile-onset SLE (j-SLE) during adulthood is poorly described. Objectives: To report adult outcome of j-SLE and compare SLE course during childhood and adulthood. Methods: j-SLE was defined as a SLE fulfilling ACR criteria and diagnosed before the age of 16 years. Mac Nemar test for paired nominal data and Wilcoxon signed rank test for paired data were used. Results: One hundred and six patients j-SLE (88 women and 18 men, female to male ratio: 4.9), mean age at diagnosis: 12.3 years were followed during a mean duration of 13.8 years, from childhood (mean: 4 years) to adulthood (mean: 10.3 years). 97.2% patients received corticosteroids (with intravenous pulses for 50.9%) and 77.3% immunosuppressant drugs. 105 (99%) patients received antimalarial drugs. Clinical manifestations of the first flare were: arthritis (67.9%), cutaneous (57.5%), nephritis (23.6%), fever (17.9%), hematologic: ITP, AIHA (15%). Neuropsychiatric manifestations were found in 6.6%. Digestive involvement was only present in 6% of cases. According to the revised SELENA FLARE INDEX (SFI), the first flare was severe for half of the patients (n=55). Disease course during adulthood had two patterns: 82 patients (77.3%) had at least one SLE flare and 24 (22.6%) a sustained remission. Mean follow up was however significantly higher in the relapsing group (15 years vs 9.8 years, p=0.0014). No difference was found between these 2 groups for first flare severity and clinical manifestations during childhood. Significantly more cutaneous (61.3 vs 42.4%, p=0.003), musculoskeletal (75.5 vs 59.4%, p=0.007), neuropsychiatric (10.4 vs 3.8%, p=0.035), or hematologic manifestations like AIHA (9.4 vs 2.8%, p=0.039) or ITP (26.4 vs 10.4%, p=0.001), and fever (32.1 vs 3.7%, p<0, 001) were observed during childhood than during adulthood. Nephritis occurred at similar frequencies in childhood and adulthood (34.9% and 30.2% respectively). Half of adulthood nephritis were relapses of j-SLE nephritis. At the end of the survey mean global SLICC damage index (SDI) was 0.64. Mean childhood SDI was lower than mean adulthood SDI (0.21 vs 0.45, p=0.016). However mean adult follow up was significantly longer. Mean SDI increase per year was similar during childhood and adulthood (0.053 vs 0.049 respectively, p=0.563). 13 patients (12.3%), had musculoskeletal damage occurring more frequently during adulthood than childhood (11 vs 2, p=0.022), specially avascular necrosis (8 vs 0, p=0.008). 5 (4.7%) patients had a renal damage that occurred mostly during adulthood (n=4). Ocular damage was present for 9 (8.5%) patients. Premature gonadal failure occurred for 5 women (5.7%). Among the 88 women 19 had 32 pregnancies, leading to 22 births. Conclusions: Damage accrual seems to increase at the same pace during childhood and adulthood. SDI was low at the end of the survey. This could reflect a protective role for HCQ, more immunosuppressant use with lower dose of steroids. Juvenile SLE nephritis are at high risk of relapsing during adulthood raising the issue of duration of immunosuppressive treatment. Disclosure of Interest: None declared